English Learners Speaking Performance: Do Self-Perception and Exteroception Influence Their Language Acquisition? - Silva Liani; Radiah Hamid (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
The research aimed to find out how students’ perception and its’ influence toward students’ speaking performance.  There were two types of perception recorded, namely self-perception and exteroception. Self-perception is a perception that is formed based on internal factors or from within , while exteroception is a perception that is formed based on external factors or from outside of a person . The research methodology  used was quantitative research. The data obtained using two instruments, namely close-ended questionnaire and students’ speaking performance score.  The data were analysed through Multiple Linear Regression Analysis . The results of data analysis from 46 samples found that 1) Students’ self-perception (72.09) and exteroception (67.85) categorized as good perception, 2) Simultaneously, self-perception and exteroception has significance influence toward speaking performance (F-test 8.73 > F-table 4.07). 3) Self-perception has significance influence toward speaking performance (T-test 2.347 > T-table 2.014), and Exteroception has no significance influence toward speaking performance   (T-test 0.590 < T-table 2.014).  Therefore, it can be concluded that students’ self-perception has the higher score than students’ exteroception. Simultaneously, both them were have significance influence toward speaking performance, while partially self-perception was the only variable has significance influence toward speaking performance. The needs and desires of students toward speaking were dominated positively. They need English speaking for their future career, which indirectly becomes motivation in speaking class.